Technical considerations in surgery for retroperitoneal sarcomas: position paper from e-surge, a master class in sarcoma surgery, and EORTC-STBSG - Bonvalot, Sylvie; Hohenberger, Peter (Annals of surgical oncology, 2012)
Background Surgery is the principal treatment for retroperitoneal sarcoma. These tumors typically involve or abut multiple organs and therefore require multivisceral resections. Despite the complexity of such operations, a standardized approach has not been described. As a result, referral centers often see patients who have undergone suboptimal surgery, with gross disease left behind. This is one of the causes of the dismal prognosis of this disease.MethodsThese consensus statements came out from E-Surge, an educational symposium with live sarcoma surgery, performed by European and North American expert sarcoma surgeons illustrating an optimal technique to an international audience, held in 2010 and 2011. The content was then shared among members of the local subcommittee of European Organization for Research and Treatment of Cancer (EORTC)-Soft Tissue and Bone Sarcoma Group (STBSG).ResultsAn attempt to describe a reproducible and standardized approach to these tumors is illustrated. A detailed description of the different procedures according to the variety of different presentations is made.ConclusionsThe approach described herein should be used as the reference standard in clinical practice and serve to perform quality check of local treatment in future trials.